Space Vector Pulse Width Modulation Method to Reducing a Switching Loss in Inverter - M.Revathi, S.; R.Balamurugan, C.; Shanmugasundaram, N. (International Journal of Engineering and Technology, 2018)
In This paper proposed an area space  vector PWM technique  that reduces switch  victims of an electrical converter  mainly efficiently by two-phase modulation technique. This technique chooses the most favorable one  that  minimizes  a replacement  switch (SW) defeat judgment  supported lessening belongings in switch period allowing for  section currents in numerous lessening patterns. This paper proposes  an  basic  curved  PWM  technique . The  planned  technique  created  it  attainable  to  scale  back  range  of  switch  of  the  biggest  or  second  major present  section .  And it will  mechanically  acclimatize  to  weight  circumstances  with  varied  power factors. Calculated switch wounded area unit condensed to regarding  50%  by the planned technique.